Kinematics of the Tucana Dwarf Galaxy: an unusually dense dwarf in the Local Group. Issue 2 (20th February 2019) - Gregory, Alexandra L; Collins, Michelle L M; Read, Justin I; Irwin, Michael J; Ibata, Rodrigo A; Martin, Nicolas F; McConnachie, Alan W; Weisz, Daniel R
Abstract: We present new FLAMES+GIRAFFE spectroscopy of 36 member stars in the isolated Local Group dwarf spheroidal galaxy Tucana. We measure a systemic velocity for the system of$v_{Tuc} = 216.7_{-2.8}^{+2.9}$ km s −1, and a velocity dispersion of$σ _{v, Tuc} = 14.4_{-2.3}^{+2.8}$ km s −1 . We also detect a rotation gradient of$\frac{{\rm d}v_{r}}{{\rm d}χ } = 7.6^{+4.2}_{-4.3}$ km s −1 kpc −1, which reduces the systemic velocity to$v_{Tuc} = 215.2_{-2.7}^{+2.8}$ km s −1 and the velocity dispersion to$σ _{v, Tuc} = 13.3_{-2.3}^{+2.7}$ km s −1 . We perform Jeans modelling of the density profile of Tucana, using the line-of-sight velocities of the member stars. We find that it favours a high central density consistent with 'pristine' subhaloes in Λ cold dark matter, and a massive dark matter halo (∼10 10 M⊙ ) consistent with expectations from abundance matching. Tucana appears to be significantly more centrally dense than other isolated Local Group dwarfs, making it an ideal laboratory for testing dark matter models.